2010
DOI: 10.1007/s11166-010-9110-0
|View full text |Cite
|
Sign up to set email alerts
|

Monetary incentives in the loss domain and behavior toward risk: An experimental comparison of three reward schemes including real losses

Abstract: International audienceIn the loss domain, both practical and ethical considerations rule out the systematic use of an incentive-compatible procedure involving real losses. The experimental study presented here aims at investigating whether some easier-to-implement procedure could be adequately used. For that purpose, the subjects' degree of risk aversion is compared across three payment conditions: a real-losses condition based on a random-lottery (incentive-compatible) system, which serves as a benchmark, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…For these reasons, we do not implement real losses in our module. Etchart-Vincent and l’Haridon (2011) have extensively tested the effect of real incentives in controlled experiments for both gains and losses, and they found that real and hypothetical choices differ significantly only in the gain domain, but not in the loss domain. 13 …”
Section: Measuring Ambiguity Attitudesmentioning
confidence: 99%
“…For these reasons, we do not implement real losses in our module. Etchart-Vincent and l’Haridon (2011) have extensively tested the effect of real incentives in controlled experiments for both gains and losses, and they found that real and hypothetical choices differ significantly only in the gain domain, but not in the loss domain. 13 …”
Section: Measuring Ambiguity Attitudesmentioning
confidence: 99%
“…Patients can be offered the possibility of gaining a reward for screening and bear a loss in the absence of screening. Despite the existence of some studies about incentive framing in other settings suggesting that loss-framed incentives are stronger motivators (Etchart-Vicent & l’Haridon, 2011; Madhavan et al, 2012), within health research there is scarce evidence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fewer studies provide evidence on the degree of loss aversion, and none of them investigate adolescents (Abdellaoui et al, 2008;Etchart-Vincent and L'Haridon, 2011). An exception is Glätzle-Rützler et al…”
Section: Descriptive Resultsmentioning
confidence: 99%